Parental experiences of providing skin-to-skin care to their newborn infant—Part 1: A qualitative systematic review - Agneta Anderzén‐Carlsson; Zeni Carvalho Lamy; Mats Eriksson (2014)
AimTo describe parental experiences of providing skin-to-skin care (SSC) to their newborn infants.BackgroundSSC care for newborn infants has been reported to have positive physiological and psychological benefits to the infants and their parents. No systematic review regarding parental experiences has been identified.DesignIn this first part of a meta-study, the findings of a systematic literature review on parental experience of SSC care are presented.Data sourcesFour databases were searched, without year or language limitations, up until December 2013. Manual searches were performed in reference lists and in a bibliography of the topic.Review methodsAfter a quality-appraisal process, data from the original articles were extracted and analysed using qualitative content analysis.ResultsThe systematic and manual searches led to the inclusion of 29 original qualitative papers from nine countries, reporting experiences from 401 mothers and 94 fathers. Two themes that characterized the provision of SSC emerged: a restoring experience and an energy-draining experience.ConclusionThis review has added scientific and systematic knowledge about parental experiences of providing SSC. Further research about fathers' experiences is recommended.